Aggregation behaviour of a single-chain, phenylene-modified bolalipid and its miscibility with classical phospholipids - Drescher, Simon; Garamus, Vasil M.; Garvey, Christopher J.; Meister, Annette; Blume, Alfred (Beilstein Journal of Organic Chemistry, 2017)
In the present work, we describe the synthesis of a single-chain, phenylene-modified bolalipid with two phosphocholine headgroups, PC-C18pPhC18-PC, using a Sonogashira cross-coupling reaction as a key step. The aggregation behaviour was studied as a function of temperature using transmission electron microscopy (TEM), differential scanning calorimetry (DSC), Fourier-transform infrared (FTIR) spectroscopy, and small angle neutron scattering (SANS). We show that our new bolalipid self-assembles into nanofibres, which transform into flexible nanofibres at 27 °C and further to small elongated micelles at 45 °C. Furthermore, the miscibility of the bolalipid with bilayer-forming phosphatidylcholines (DMPC, DPPC, and DSPC) was investigated by means of DSC, TEM, FTIR, and small angle X-ray scattering (SAXS). We could show that the PC-C18pPhC18-PC is partially miscible with saturated phosphatidylcholines; however, closed lipid vesicles with an increased thermal stability were not found. Instead, bilayer fragments and disk-like aggregates are formed.
Keywords: aggregation behaviour; bolaamphiphiles; bolalipids; membrane lipids; mixing behaviour; nanofibres; self-assembly